The fitting effects between strategic flexibility and managerial ties on green innovation in new ventures - Chen, Haowen (Frontiers in Environmental Science, 2022)
Green innovation is a key variable in coordinating economic growth and ecological protection, and also the fundamental driving force for future economic development. Green innovation plays a crucial role in creating competitive advantages for companies. This paper investigates the impact of the interaction between strategic flexibility and managerial ties on green innovation in new firms, and explores ways to match strategic flexibility and managerial ties that are more appropriate for conducting green innovation practices. The results of the empirical study by using survey data from Chinese new firms indicate that different types of strategic flexibility and managerial ties can generate different synergies and thus have different impacts on green innovation. Specifically, for a new venture, it is more likely to use its ties with government to develop green innovation when it has greater resource flexibility. Conversely, a new venture with greater coordination flexibility is more capable of implementing green innovation through close ties with other firms. Our theoretical constructs and empirical results can better explain how different types of strategic flexibility use different kinds of managerial relationships to promote green innovation in new ventures.